Adherence to Community Acquired Pneumonia guideleines and patients outcomes in a peri-urban hospital in Natal, South Africa - Waheeba Madani; Halima Dawood (Journal of Infection in Developing Countries)
Introduction: Community-acquired pneumonia (CAP) is an important cause of mortality and morbidity worldwide. This issue is further exacerbated by the Human Immunodeficiency Virus (HIV) epidemic.